Modern artistic literature about the village: geographical aspect - Krylova Maria Nikolaevna (Institute of Modern Humanitarian Researches, 2022)
The article examines modern literature about the village from the point of view of the place of birth of the authors and the place of action in their works. The purpose of the article was to identify the features of modern prose about the countryside, determined by the geography of their creation. The research was carried out using historical-genetic, sociological, biographical, descriptive and other methods. The greatest attention was paid to the works by V.V. Lichutin, B.P. Ekimov, A.V. Novoseltsev, A.G. Bayborodin, M.A. Tarkovsky, V.O. Avchenko, L. Beloivan and others, and the analysis was carried out from the point of view of reflection in the prose of the authors' data on geographical realities and a special local perception of reality. It is noted that many components of the narrative depend on geographic affiliation, which influences the formation of a specific picture of the world of a particular writer, on his social and life experience, largely related to his place of residence. The strongest segment of modern literature about the village is the northern text, which is demonstrated by the following of writers who turned to the theme of the village, the traditions of “village prose”. In addition, the literature about the village, created in the south of Russia, in Siberia and the Far East, is highlighted. It is concluded that in the literature about the village, the geographical factor turns out to be very strong and more significant than in other thematic layers of modern Russian literature, since it is in the texts about the village that authors are most focused on expressing their geographical preferences, analysing reality that has a local colouring. Geographical realities shape the originality of works about the modern village and create a unique context for their creation.